Technology Integration in The Hannafin and Peck Model: Dynamic Transformation of Islamic Religious Education at Sdn Cilengkrang - Nurhasanah, Lilis Romdon; Mulyawan Safwandy Nugraha; Ujang Dedih (Indo-MathEdu Intellectuals Journal, 2024)
This research adopts a qualitative approach, employing a case study method to explore the impact of technology integration in the teaching of Islamic Religious Education (PAI) at SDN Cilengkrang. Data collection is conducted through interviews, observations, and document analysis to gain deep insights into the experiences of teachers and students regarding the instructional model that incorporates technology. The research aims to provide a detailed understanding of how technology, including PAI software and online platforms, influences the engagement and comprehension of religious concepts among students. The data analysis process in this study is inductive, where researchers systematically explore patterns, themes, and relationships emerging from interviews, observations, and document analysis. Thus, the research aims to comprehensively describe the positive impact of technology integration in PAI learning. The findings of this research support existing literature and emphasize the potential of dynamic PAI learning, integrating cognitive aspects with religious values. The success of technology integration in PAI teaching at SDN Cilengkrang, despite facing challenges in teacher training, has significant positive implications. Serving as a foundation for improving the quality of PAI teaching, this research opens new opportunities for more dynamic and holistic learning experiences.